Discovery of a DNA methylation episignature for Weiss-Kruszka syndrome - Haley McConkey; Liselot van der Laan; Sourav Ghosh; Lotte Kleinendorst; Michael A. Levy; Jessica Rzasa; Johanna M. van Hagen; Quinten Waisfisz; Heidi L. Schulz; Corina Heller; Kerstin Huhn; Carolin D. Obermaier; et al. (Human Genetics, 2026)
Weiss-Kruszka syndrome (WSKA; OMIM 618619) is a rare autosomal dominant neurodevelopmental disorder caused by haploinsufficiency of ZNF462, a zinc-finger transcription factor involved in chromatin regulation and early embryonic development. WSKA is characterized by developmental delay, hypotonia, craniofacial dysmorphic features (around 8) and variable congenital anomalies. Genome-wide DNAm profiling was performed on peripheral blood DNA from 9 WSKA cases with (likely) pathogenic ZNF462 variants and matched controls to look for differential methylation. Analysis using the EpiSign™ pipeline identified a robust DNAm pattern, or episignature, specific to WSKA syndrome. Supervised machine-learning classification demonstrated high sensitivity and specificity, with reproducibility confirmed by leave-one-out cross-validation, as well as correctly classifying a validation case with a pathogenic ZNF462 variant. Comparative analysis revealed partial overlap of genome-wide DNA methylation changes between the WSKA episignature and other neurodevelopmental disorders involving chromatin regulators. Functional annotation of differentially methylated probes and regions demonstrated enrichment for pathways related to neurodevelopment, neuron function and cell adhesion. These findings define and validate a distinct DNAm episignature for WSKA, providing a valuable diagnostic biomarker to support variant classification and offering insight into the epigenomic consequences of ZNF462 haploinsufficiency.